A study of a single variant allele (rs1426654) of the pigmentation-related gene SLC24A5 in Greek subjects - Dimisianos, G.; Stefanaki, I.; Nicolaou, V; Sypsa, V; Antoniou, C.; Poulou, M.; Papadopoulos, O.; Gogas, H.; Kanavakis, E; Nicolaidou, E.; Katsambas, A. D.; Stratigos, A. J. (Exp DermatolExp DermatolExp Dermatol, 2009)
The SLC24A5 gene, the human orthologue of the zebrafish golden gene, has been shown to play a key role in human pigmentation. In this study, we investigate the prevalence of the variant allele rs1426654 in a selected sample of Greek subjects. Allele-specific polymerase chain reaction was performed in peripheral blood samples from 158 attendants of a dermatology outpatient service. The results were correlated with pigmentary traits and MC1R genotype. The vast majority of subjects (99%) were homozygous for the Thr(111) allele. Only two subjects from the control group (1.26%) were heterozygous for the alanine and threonine allele. Both of these Thr(111)/Ala(111) heterozygotes carried a single polymorphism of MC1R (one with the V92M variant and another with the V60L variant). Following reports of the rs1426654 polymorphism reaching fixation in the European population, our study of Greek subjects showed a prevalence of the Thr(111) allele, even among subjects with darker skin pigmentation or phototype.
Keywords: *Alleles; Adult; Antiporters/*genetics; Case-Control Studies; Female; Greece; Humans; Male; Middle Aged; Polymorphism, Genetic/*genetics; Receptor, Melanocortin, Type 1/genetics; Skin Pigmentation/*genetics